2015
DOI: 10.5194/bg-12-7107-2015
|View full text |Cite
|
Sign up to set email alerts
|

Ocean dynamic processes causing spatially heterogeneous distribution of sedimentary caesium-137 massively released from the Fukushima Daiichi Nuclear Power Plant

Abstract: Abstract. Massive amounts of anthropogenic radiocaesium 137Cs that were released into the environment by the Fukushima Daiichi Nuclear Power Plant accident in March 2011 are widely known to have extensively migrated to Pacific Ocean sediment off of eastern Japan. Several recent reports have stated that the sedimentary 137Cs is now stable with a remarkably heterogeneous distribution. The present study elucidates ocean dynamic processes causing this heterogeneous sedimentary 137Cs distribution in and around the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…It can be the result of both local heterogeneities of sediment features [11] and the bottom topography [39]. To separate the topography effect from the effects of transport, erosion and deposition of contaminated sediments on the exchange of activity between the seafloor and water, consider the idealized case of a straight channel with a bottom depression (Fig.…”
Section: Radionuclide Transport In a Channel With Bottom Depressionmentioning
confidence: 99%
See 2 more Smart Citations
“…It can be the result of both local heterogeneities of sediment features [11] and the bottom topography [39]. To separate the topography effect from the effects of transport, erosion and deposition of contaminated sediments on the exchange of activity between the seafloor and water, consider the idealized case of a straight channel with a bottom depression (Fig.…”
Section: Radionuclide Transport In a Channel With Bottom Depressionmentioning
confidence: 99%
“…Unlike other radioactivity transport models [2,11], the exchange rate W pw ð0;1Þ (mass transfer coefficient [7]) is estimated by boundary layer theory [34] and corrected for surface roughness [10] as…”
Section: The Equations Of Radionuclide Transportmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have investigated the 137 Cs budget in the sediment off Fukushima (Ambe et al 2014;Black and Buesseler 2014;Otosaka and Kato 2014;Higashi et al 2015), but because the sampling area and timing differed among these studies, it is difficult to compare the data to clarify the fate of FDNPP-derived 137 Cs in the sediment. In the Irish Sea, MacKenzie et al (1994) reported that sediment contaminated by radionuclides from the Sellafield nuclear fuel reprocessing plant is redistributed mainly with silt-sized sediment particles, and dissolution of 137 Cs from the sediment may also play an important role in post-depositional migration of 137 Cs (e.g., Cook et al 1997;MacKenzie et al 1998).…”
mentioning
confidence: 99%
“…Long-term monitoring of bottom waters just above the seafloor and field experiments carried out off the Fukushima coast revealed that the combination of wave and current action caused by meteorological disturbance was a key process in the transport of suspended particulate material (Yagi et al 2015;Buesseler et al 2015). On the basis of a numerical simulation, Higashi et al (2015) suggested that the shape of the high-concentration band in the southern area (the "hotspot swath") mainly reflected spatiotemporal variation in bottom shear stress between the shallow shelf (<50 m water depth) and the area offshore of the shelf break. These proposals are all based on data obtained during a relatively restricted time span after the accident (~1 year), so longterm trends of 137 Cs deposition and transport in the area are not yet known.…”
mentioning
confidence: 99%